Penentuan Kandungan Radionuklida Alam dan Unsur Logam pada Tanah Pertanian Desa Tiga Panah, Kab. Karo, Sumatera Utara Dengan Menggunakan Metode XRF - Reh Malem br Karo (Universitas Prima Indonesia, 2020)
The aim of this study to monitoring radionuclide and elemental composition of agricultural soils from sub district Tiga Panah, Karo Regency, North Sumatera, Indonesia. This study using XRF spectrometric method. The natural radionuclides found in four types of soil samples (soil of chili (Capsicum annum L) code B1, soil of Corn (Zea Mays) ) code B2, soil of Broccoli (Brassica oleracea Â L.)) ) code B3 and soil control (code B4) were Thorium and Uranium. The concentration of ThÂ were 27,5 mg/kg; 19,8mg/kg, 22,6 mg/kg; 24,7 mg/kg, respectively and the concentration of Uranium were 3,1mg/Kg;<0,4 mg/kg;4,9 mg/kg;3,1mg/kg, respectively. Some mean concentrations of these radionuclides are comparable to values from other locations around the world and the others higher. The XRF analysis revealed some elements in agricultural soil sub district Tiga Panah, Karo namely K, P, Ca, Cr, Mn, Fe, Co,Al, Na, Mg, Si, Cu and Zn. The concentration of Aluminium, Silicate and Phospor were found higher than the other elements Keywords: Radionuclide, XRF, Â Agricultural Soil, Metal